Gastrodin attenuates renal injury and collagen deposition via suppression of the TGF-β1/Smad2/3 signaling pathway based on network pharmacology analysis - Wen, Ying; Zhang, Xiuli; Wei, Lihui; Wu, Meizhu; Cheng, Ying; Zheng, Huifang; Shen, Aling; Fu, Changgeng; Ali, Farman; Long, Linzi; Lu, Yao; Li, Jiapeng; et al. (Frontiers in Pharmacology, 2023)
Background: Gastrodin has been widely used clinically in China as an antihypertensive drug. However, its effect on hypertensive renal injury is yet to be elucidated. The current study aimed to investigate the effects of gastrodin on hypertensive renal injury and its underlying mechanisms by network pharmacology analysis and validation in vivo and in vitro. Methods: A total of 10 spontaneously hypertensive rats (SHRs) were randomly categorized into the following two groups: SHR and SHR + Gastrodin groups. Wistar Kyoto (WKY) rats were used as the control group (n = 5). The SHR + Gastrodin group was intragastrically administered gastrodin (3.5 40mg/kg/day), and the rats in both WKY and SHR groups were intragastrically administered an equal amount of double-distilled water for 10 weeks. Hematoxylin-eosin, Masson’s trichrome, and Sirius red stainings were used to detect the pathological changes and collagen content in the renal tissues. Network pharmacology analysis was performed to explore its potential targets and related pathways. In vitro, the CCK-8 assay was used to determine the cell viability.Immunohistochemistry and western- blotting analyses were employed to assess the protein expression associated with renal fibrosis and transforming growth factor-β1 (TGF-β1) pathway-related proteins in the renal tissues or in TGF-β1-stimulated rat kidney fibroblast cell lines (NRK-49F). Results: Gastrodin treatment attenuates renal injury and pathological alterations in SHRs, including glomerular sclerosis and atrophy, epithelial cell atrophy, and tubular dilation. Gastrodin also reduced the accumulation of collagen in the renal tissues of SHRs, which were confirmed by down-regulation of α-SMA, collagen I, collagen III protein expression. Network pharmacology analysis identified TGFB1 and SMAD2 as two of lead candidate targets of gastrodin on against hypertensive renal injury. Consistently,gastrodin treatment down-regulated the increase of the protein expression of TGF-β1, and ratios of both p-Smad2/Smad2 and p-Samd3/Smad3 in renal tissues of SHRs. In vitro, gastrodin (25-100 μM) treatment significantly reversed the upregulation of α-SMA, fibronectin, collagen I, as well as p-Smad2 and p-Smad3 protein expressions without affecting the cell viability of TGF-β1 stimulated NRK-49F cells. Conclusion: Gastrodin treatment significantly attenuates hypertensive renal injury and renal fibrosis and suppresses TGF-β1/Smad2/3 signaling in vivo and in vitro.